2020
DOI: 10.1016/j.arth.2020.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Preoperative Pain Sensitivity Predicts the Postoperative Analgesic Requirement and Recovery after Total Knee Arthroplasty: A Prospective Study of 178 Patients

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Prospective identification of these challenges, including the application of standardized cognitive and psychosocial assessments, can allow for appropriate preoperative referral, patient optimization, and future study of risk mitigation strategies [15,18,52,75,78,80,88]. To this end, various predictive tools for postoperative pain are being explored [88][89][90][91]. Patient-centered education and expectation management during the pre-admission phase of care are effective strategies for improving postoperative pain control, limiting postoperative opioid use, decreasing complications and readmissions, and increasing postoperative function and quality of life [15,18,[92][93][94][95][96][97][98].…”
Section: Patient Pain History Evaluation and Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…Prospective identification of these challenges, including the application of standardized cognitive and psychosocial assessments, can allow for appropriate preoperative referral, patient optimization, and future study of risk mitigation strategies [15,18,52,75,78,80,88]. To this end, various predictive tools for postoperative pain are being explored [88][89][90][91]. Patient-centered education and expectation management during the pre-admission phase of care are effective strategies for improving postoperative pain control, limiting postoperative opioid use, decreasing complications and readmissions, and increasing postoperative function and quality of life [15,18,[92][93][94][95][96][97][98].…”
Section: Patient Pain History Evaluation and Educationmentioning
confidence: 99%
“…Prospective identification of these challenges, including the application of standardized cognitive and psychosocial assessments, can allow for appropriate preoperative referral, patient optimization, and future study of risk mitigation strategies [ 15 , 18 , 52 , 75 , 78 , 80 , 88 ]. To this end, various predictive tools for postoperative pain are being explored [ 88 , 89 , 90 , 91 ].…”
Section: Pain Management and Opioid Stewardship Across The Periopementioning
confidence: 99%
“…15,16 There is only one study that investigated the pain condition using an algometer. 7 In that study, patients with higher preoperative VAS scores had higher acute postoperative pain, requiring a higher dosage of analgesics in the immediate postoperative period, which predicted PT evaluation. Additionally, these authors emphasized that patients with a low PT should be counseled preoperatively and should receive more meticulous treatment of analgesics perioperatively.…”
Section: Discussionmentioning
confidence: 84%
“…6 To our knowledge, only one study has investigated the pain condition using an algometer and postoperative pain and the analgesic requirement on the day of surgery and during the postoperative period. 7 Unlike the above-cited study, in this study we evaluated the effect of using a tourniquet on early-stage pain and 1-year postoperative functional outcomes when patients were divided into two groups according to the PT.…”
mentioning
confidence: 99%
“…With regard to regional anesthesia, a double-blinded RCT demonstrated that spinal anesthesia with mepivacaine yielded a more predictable return of motor function than low-dose bupivacaine; both interventions had a similar safety profile 34 . Finally, a prospective study of 178 patients revealed that a preoperative assessment of pain sensitivity predicts postoperative analgesic requirements 35 . It is important to keep in mind that considerable variability exists in baseline pain sensitivity between patients.…”
Section: Anesthesia and Pain Managementmentioning
confidence: 99%